Fundamentals of Male Infertility - Silber, Sherman (Springer International Publishing, 2018)
This book analyzes the basic science and treatment of male factor infertility with Dr. Silber's characteristic honesty and clear thinking. It describes finally what works and what doesn't work. It will inspire everyone in reproductive medicine (Gynecologists, Urologists, Embryologists and Endocrinologists) who wish to better understand male infertility.